ABDULLA ORIPOV SHE’RIYATIDA UMUMINSONIY QADRIYATLAR TALQINI - Kenjaev, F. (SCIENCE and SOCIETY, 2018)
The article deals with the analysis of artistic deseription of human problems in Uzbek literature and individual creative peculiarities of writers. The object of thoretical and practical analysis was the creative work of the famous Uzbek poet A.Oripov.